S65 Interim data from a randomised controlled trial of average volume-assured pressure support (AVAPS) versus spontaneous-timed (ST) pressure support in Obesity Hypoventilation Syndrome (OHS). (16th November 2010) - Murphy, P; Davidson, A C; Williams, A J; Moxham, J; Simonds, A; Hind, M; Polkey, M I; Hart, N
Abstract : Introduction: The obesity epidemic is leading to an increase in respiratory morbidity including sleep disordered breathing (SDB). The optimal ventilatory strategy in OHS is yet to be characterised. Changes in the respiratory system compliance through sleep and positional variations could compromise the effectiveness of fixed level pressure support thus the idea of varying pressure support to maintain tidal volume is appealing. Published data show improvements in nocturnal control of SDB in OHS using AVAPS mode ventilation (Storre et al, 2006) but also concerns regarding sleep fragmentation (Janssens et al, 2009). Data from these studies have been difficult to interpret as patient set up has not been set out to minimise the differences between modes. Method: Consecutive patients admitted for setup of domiciliary NIV were randomised to either ST or AVAPS mode (BiPAP Synchrony, Philips-Respironics, Murrysville, USA). NIV was titrated to improve nocturnal oximetry-capnometry using a standard setup protocol. Patients had baseline investigations including anthropometrics, health related quality of life and gas exchange. A subset of patients had sleep disruption monitored via actigraphy (AW64, Philips-Respironics, Murrysville, USA) in the week following discharge. Results: 50 patients were enrolled, mean age 55±11 years, 53% male, BMI 50±7 kg/m 2, PaCO2 6.85±0.81 kPa, PaO2 8.91±1.55 kPa, ESS 12±6 with preliminary data available at 6 weeks for 43 patients, 13 were initiated acutely and 30 were elective admissions. No significant between group differences (Abstract S65 Table 1 ). Actigraphy analysis (AVAPS n=16, ST n=17) during 1st week of NIV showed total sleep time of 347±80 min in AVAPS and 348±78 min in ST with sleep efficiency of 81±6% in AVAPS and 79±12% in ST. Arterial blood gas analysis at 6 weeks showed no between group differences. However, significant improvement occurred in PaCO2 in AVAPS patients, mean difference 0.63 kPa (p=0.013), that did not reach significance in ST, mean difference 0.55 kPa (p=0.053). Conclusion: The preliminary data indicate no significant sleep disruptive effect of AVAPS mode compared to ST following initiation of NIV for OHS. There was no clinically significant difference between groups in the primary outcome of change in PaCO2, although there was only a significant fall in PaCO2 in the AVAPS group. 3 months data are awaited.